دابه شبونی جوگرافی پروژه کانی نیشته جیبونی ستونی له شاری سلیمانی له سالی ۲۰۲۰ - حسین, پ.ی.د. بەیان علی; توفیق, م.ی. كامران محمد (Sulaimani Journal for Humanities, 2023)
The research tackles the distribution of vertical residential projects in Sulaimani in 2020, as an attempt at introducing and illustrating the ways of their distribution in the city. The research adopts the descriptive-analytic method as well as the use of (GIS). It first sheds light on the residential projects concerning the body responsible for implementing the projects, as it appears, three different bodies are in charge of constructing vertical residential buildings in Sulaimani; Presidency of Sulaimani Municipality, Directorate of Construction and Housing, and Directorate of Investment. Overall there are 54 projects; 37 of them consist of vertical residential projects and the other 17 include both vertical and horizontal housing. The majority are investment projects, with 38 in total, then private properties with 10 projects, and only 6 projects implemented by Directorate of Construction and Housing. Of the most significant conclusions the research has reached is the unbalancing distribution of the projects among the various directorates of municipalities in the targeted zone; most of them are in the zone of Rozhalat municipality with 20 projets, and the least are in Bakrajo and central municipality with only one project. Furthermore, the distribution of the projects is random to an extent, spreading mostly to the south-east of the city
Keywords: Vertical housing; geographical distribution; housing investment; Sualimanimunicipality